2020
DOI: 10.1001/jamainternmed.2019.4317
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Work-Related Burnout in Physician-Scientists Receiving Career Development Awards From the National Institutes of Health

Abstract: Wide rate variation also suggests the need for caution and pacing in GME payment reform, with attention to how payment reductions may affect hospitals receiving lower payments.Study limitations included analysis of Medicare GME support, not actual training costs, and we did not examine additional hospital characteristics that may contribute to GME payment variation or Medicaid GME payments.Capping the Medicare GME payment rate would be a limited reform. More comprehensive approaches would involve rethinking GM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…Degree of burnout was assessed using a translated Japanese version of the Copenhagen Burnout Inventory (CBI) [ 18 , 19 ]. The CBI, which has recently been used to measure burnout among medical physicians [ 20 , 21 ], is a nineteen-item survey for assessing three burnout subscales: personal (6 items), work-related (7 items), and client-related burnout (6 items). Cronbach’s alpha was estimated for each subscale.…”
Section: Methodsmentioning
confidence: 99%
“…Degree of burnout was assessed using a translated Japanese version of the Copenhagen Burnout Inventory (CBI) [ 18 , 19 ]. The CBI, which has recently been used to measure burnout among medical physicians [ 20 , 21 ], is a nineteen-item survey for assessing three burnout subscales: personal (6 items), work-related (7 items), and client-related burnout (6 items). Cronbach’s alpha was estimated for each subscale.…”
Section: Methodsmentioning
confidence: 99%
“…The changing dynamics in health care that contribute to physician burnout also complicate the experience of individuals who navigate the dual arenas of clinical medicine and biomedical research. The most recent comprehensive study on burnout among physician-scientists surveyed 816 physician-scientists 5–8 years after K-level funding (42% women) and showed that 42% of women spent more than 44 hours per week on domestic tasks compared with 17% of men ( 33 ). Women also had a lower appraisal of their work climate, worked fewer overall work hours, and were more likely than men to report burnout ( 33 ).…”
Section: The Challengesmentioning
confidence: 99%
“…The most recent comprehensive study on burnout among physician-scientists surveyed 816 physician-scientists 5–8 years after K-level funding (42% women) and showed that 42% of women spent more than 44 hours per week on domestic tasks compared with 17% of men ( 33 ). Women also had a lower appraisal of their work climate, worked fewer overall work hours, and were more likely than men to report burnout ( 33 ). These disparities pose challenges for career advancement of women in the PSW and require awareness by both institutions and funding agencies.…”
Section: The Challengesmentioning
confidence: 99%
“…[2][3][4] The studies cited here have further suggested that work−life integration is a common concern, 5 and gender differences in domestic responsibilities 6 appear to be associated with gender differences in burnout among academic physicians. 7 However, little is known about work−life integration experiences in the field of medical physics, how they might differ by gender, or how they may relate to well-being or success of those pursuing this important career path.…”
Section: Introductionmentioning
confidence: 99%